Synthesis of Titanium Dioxide Nanotubes with Different N-Containing Ligands via Hydrothermal Method - Cheng Yee Leong; Ye Shen Lo; Pei Wen Koh; Siew Ling Lee (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Titanium dioxide (TiO2) nanotubes (TNT) were successfully synthesized using different N-containing ligands via hydrothermal method. Methylamine, ethylenediamine and diethylenetriamine with different Ti/ligand molar ratios (1:1, 1:3, 1:5 and 1:8) were prepared. As-synthesized TiO2 without N-containing ligands were also prepared for comparison purpose. The X-Ray Diffraction patterns confirmed the presence of anatase phase of TiO2 in all the synthesized samples whereas the presence of sodium titanate was only detected in the samples containing N-containing ligands. The Transmission Electron Microscopy images also showed that the N-containing ligands promoted the formation of nanotubes in the anatase TiO2. Based on the Tauc Plot, the band gap energy of anatase TiO2 was shifted with the addition of methylamine, ethylenediamine and diethylenetriamine. The photoluminescence spectra also showed that with the addition of sufficient amount of N-containing ligands, the intensity of photoluminescence spectrum decreased, suggesting formation of more nanotube and reduction of electron hole recombination rate. The photocatalytic performance of all synthesized samples was determined through photodegradation of Congo red under UV light for 6 hours. The results suggested that among the synthesized materials, the sample which contained diethylenetriamine with molar ratio of 5 gave the highest photocatalytic activity of 76.71% which could be attributed to successful formation of nanotube, its higher surface rate reaction and low electron hole recombination. Diethylenetriamine showed higher efficiency in assisting the formation of TiO2 nanotubes compared to methylamine and ethylenediamine.